النشاطات العلاجية الدينية في المدينة الجزائرية - درنوني, سارة; لغريبي, نسيمة (جامعة الوادي - University of Eloued, 2022)
اهتمت هذه الدراسة الميدانية في البحث حول أسباب توجه الأفراد نحو النشاطات العلاجية الدينية في المدينة الجزائرية، على الرغم من أن البيئة الحضرية طاردة لهذه النشاطات الا أن الطبيعة الثقافية والاجتماعية للمجتمع الجزائري، وغياب قانون صريح يحدد منعها، سمح بانتشار مختلف عيادات الرقية والحجامة والعلاج بالأعشاب، وهذا التواجد ليس الا ترجمة للإقبال الهائل نحوها. أجريت الدراسة على عينة بحث في مدينة باتنة، حددت العينة بأفراد يتوجهون الى هذه النشاطات لطلب التشخيص والعلاج، بهدف تحديد مختلف الأسباب الثقافية والاجتماعية التي تؤدي بهم الى التوجه الى النشاطات العلاجية الدينية. This study interestss in research on the reasons for individuals heading towards religious healing activities in the Algerian city, although the urban environment repels these activities, but the cultural and social nature of Algerian society, and the absence of an explicit law determining their prevention, allowed the spread of various clinics of ruqyah, cupping and herbal therapy, and this Presence is nothing but a translation of the huge people who goes towards it. The study was conducted on a research sample in the city of Batna, and it identified treatment for individuals who go to these activities to seek diagnosis and treatment, to try to determine the various cultural and social reasons that lead them to go to religious remedial activities.
دراسة ميدانية بمدينة باتنة
مقال
Keywords: المدينة الجزائرية ; النشاطات الدينية ; النشاطات العلاجية; Curative activities; religious activities; the Algerian city